Strategies for palladium-catalyzed non-directed and directed C-H bond functionalization - Kapdi, Anant R.; Maiti, Debabrata (Amsterdam Elsevier, 2017)
Strategies for Palladium-Catalyzed Non-directed and Directed C-H Bond Functionalization portrays the complete scope of these two aspects of C-H bond functionalization in a single volume for the first time. Featured topics include the influence of palladacyclic systems in C-H bond functionalization (need for newer catalytic systems for better efficiency), mechanistic aspect of the functionalization strategies leading to better systems, and applications of these methodologies to natural product synthesis and material synthesis.--Provided by publisher.
Chapter 1 - Introduction -- Chapter 2 - Directed Csingle bondH Bond Functionalization Strategies for Synthesis -- Chapter 3 - Nondirected Csingle bondH Bond Functionalizations of (Hetero)arenes -- Chapter 4 - Palladium-Catalyzed Directed Arylation of Unactivated C(sp3)single bondH Bonds -- Chapter 5 - Csingle bondH Bond Functionalization at the Benzene Core of Indoles and Indolines (Excluding C-2 and C-3) -- Chapter 6 - Palladium-Catalyzed Carbonylative and Carboxylative Csingle bondH Functionalization Reactions: Importance and Role of Regioselectivity -- Chapter 7 - Flow Chemistry Perspective for Csingle bondH Bond Functionalization -- Chapter 8 - Directed Meta-Selective Csingle bondH Bond Functionalizations -- Chapter 9 - Recent Advances in Distal Aliphatic sp3 Csingle bondH Functionalization -- Chapter 10 - Palladacycles for Directed and Nondirected Csingle bondH Bond Functionalization of (Hetero)arenes -- Chapter 11 - Mechanistic/Organometallic Aspects of Palladium-Catalyzed Csingle bondH Bond Functionalization -- Chapter 12 - Recent Developments in Palladium-Catalyzed Natural Product Synthesis via Csingle bondH Activation -- Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Palladium catalysts; Homogeneous catalysis; Hydrocarbons; Activation (Chemistry); Organometallic chemistry; Electronic books